Net health benefit of mavacamten for the treatment of Chinese patients with obstructive hypertrophic cardiomyopathy: a model-based economic evaluation - Bao, Han; Jia, Yu; Wang, Xingzhi; Hurst, Michael; Cheah, Zoe; Ho, Melissa; Xuan, Jianwei (Frontiers in Pharmacology, 2025)
ObjectiveObstructive hypertrophic cardiomyopathy (HCM) is a cardiovascular disorder characterized by significant symptom burden. This study aims to evaluate the net clinical benefit of mavacamten (a first-in-class cardiac myosin inhibitor) ± beta-blockers/calcium channel blockers (BB/CCBs) compared to BB/CCB monotherapy for Chinese patients with obstructive HCM.MethodsA five-state Markov model (NYHA classes I–IV and death) was developed from a Chinese healthcare system perspective. Patients were initialised in NYHA II or III states, mirroring the baseline distribution in the EXPLORER-CN trial (NCT05174416). State transitions were simulated using cycle-specific probabilities derived from trial data and validated extrapolation assumptions. All-cause mortality risks incorporated disease-specific and extra surgical mortality rates. Treatment sequencing rules reflected escalation pathways (e.g., non-response, adverse events, or eligibility for septural reduction therapy [SRT]), informed by Chinese clinical practice. Health utilities were mapped algorithmically from EXPLORER-CN patient-level EQ-5D responses.ResultsOver a lifetime horizon, mavacamten ± BB/CCBs demonstrated superior health outcomes versus BB/CCB monotherapy, with incremental gains in life-years (15.76 vs. 14.40) and quality-adjusted life-years (QALYs: 13.69 vs. 11.38).ConclusionMavacamten provides substantial health benefits for Chinese obstructive HCM patients, including clinically meaningful improvements in survival and quality-of-life metrics relative to standard care.